Výuka o vědě a jejích dějinách: Česko versus Západ - Jana Poupová (Karolinum Press, 2018)
This study deals with learning about science and its history. It is based on an instrumental conception of the history of science; i. e. history of science is believed to be very instructive as far as the nature of science is concerned. To give pupils insight into the benefits as well as the limits of the scientific way of thinking is considered to be a very important goal of science education. In order to achieve this goal many countries recommend teaching the history of science as a part of the so-called STS education. This article describes how Czech curriculum refers to this issue at both the primary and secondary school levels. The Czech situation is discussed in comparison to that of several English-speaking countries (Great Britain, USA and Canada). Documents of the International History, Philosophy and Science Teaching Group and of the European Union were used for this purpose. The study shows that Czech education deals especially with scientific methodology and does not pay enough attention to interactions between science and society nor to the nature of scientific knowledge. Teaching history of science is recommended to improve this. It is necessary to embody the history of science not only into curriculum documents, but also into textbooks and teachers' educational programmes.